Drying of licorice root by novel radiative methods. Issue 3 (19th January 2021) - Icier, Filiz; Ozmen, Duygu; Cevik, Mutlu; Cokgezme, Omer Faruk
Abstract: In this study, licorice root was successfully dried using two different radiative dryers (Carbon fiber‐assisted cabin drying‐CFACD and infrared drying‐ID), and their effects on some drying characteristics, quality properties, and energy‐exergy efficiency were investigated. Page and Verma models were the best models describing the drying behavior of licorice root for CFACD and ID methods, respectively. ID protected total phenolic content (TPC) better than CFACD while the changes of color properties were higher for ID. Energy and exergy efficiencies of CFACD were 40.20 ± 0.20% and 31.87 ± 0.10%, respectively, while these values were 10.39 ± 0.33% and 9.99 ± 0.27% for ID, respectively. Practical applications: The radiative heating method has advantages such as shorter drying time, high‐energy efficiency, and high heat transfer coefficient compared to convective drying methods. Infrared drying (ID) is known as the common energy efficient drying method for food materials while the information on the performance of other type of radiative carbon fiber assisted drying (CFACD) systems is limited. In this study, the use of carbon fiber assisted cabin dryer for drying of licorice was evaluated by comparing other radiative type infrared dryer. The drying characteristics of licorice samples having high amount of phenolic contents were compared both in terms of quality and energy performance characteristics of dryers. Energy and exergy efficiencies of CFACD were found to be higher than ID. In addition, more homogeneous temperature distribution and less color change were obtained in the CFACD process. It was determined that the CFACD process could be recommended for drying of licorice samples rather than ID.